2017
DOI: 10.1063/1.5006551
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced exchange bias in MnN/CoFe bilayers after high-temperature annealing

Abstract: We report an exchange bias of more than 2700 Oe at room temperature in MnN/CoFe bilayers after hightemperature annealing. We studied the dependence of exchange bias on the annealing temperature for different MnN thicknesses in detail and found that samples with t MnN > 32 nm show an increase of exchange bias for annealing temperatures higher than T A = 400 • C. Maximum exchange bias values exceeding 2000 Oe with reasonably small coercive fields around 600 Oe are achieved for t MnN = 42, 48 nm. The median block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…However, the spin orientation is controversial and might depend critically on the lattice constants. In previous studies, some of the authors of this article have shown its utility for exchange bias applications with large exchange bias fields at room temperature [22][23][24][25][26][27]. However, the critical thickness for the onset of exchange bias was observed to be around 10 nm at room temperature, leading to the conclusion that MnN has a small magnetocrystalline anisotropy energy density [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the spin orientation is controversial and might depend critically on the lattice constants. In previous studies, some of the authors of this article have shown its utility for exchange bias applications with large exchange bias fields at room temperature [22][23][24][25][26][27]. However, the critical thickness for the onset of exchange bias was observed to be around 10 nm at room temperature, leading to the conclusion that MnN has a small magnetocrystalline anisotropy energy density [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, further work is required for the optimization of the growth conditions of this alloy. For instance, controlling the N/Ar mixture during deposition can result in loop shifts in excess of 2.7 kOe at room temperature and an enhanced thermal stability and median blocking temperature >450 K for compositionally identical structures [17]. A critical difference between the behavior of MnN and IrMn is that the peak in the loop shift as a function of t AF occurs at much lower thicknesses (~8 nm) for the latter.…”
Section: Exchange Bias: In-plane Studiesmentioning
confidence: 99%
“…However, further work is required for the optimization of the growth conditions of this alloy. For instance, controlling the N/Ar mixture during deposition can result in loop shifts in excess of 2.7 kOe at room temperature and an enhanced thermal stability and median blocking temperature > 450 K for compositionally identical structures [17].…”
Section: Exchange Bias: In-plane Studiesmentioning
confidence: 99%
“…It should be noted that most of the theoretical models for EB properties do not account for thermal effects [5][6][7][8][9]. Recently, many experimental studies were conducted to well understand the thermal effects on the EB properties and they have shown some common behaviors of EB properties and some contradictory behaviors [10][11][12][13][14][15][16][17]. The main common behavior is that the exchange field HE and the coercive field HC decrease as the temperature increases at low temperatures.…”
Section: Introductionmentioning
confidence: 99%